Polygamy and Its Impact on the Mental Health of Family Members: Implications for Counseling Practice - Abd Razak, Muhammad Ajib (International Journal of Psychosocial Rehabilitation, 2020)
Polygamous marriage remains a controversial issue in various societies. Nonetheless, this practice is considered legitimate and allowed in many countries, most commonly in Muslim-majority countries. Although polygamy is accepted by numerous communities around the globe, others view this practice as irrational, oppressive towards women and children, a cause of family problems such as conflict, divorce, neglect of responsibility and absent fathers, as well as a source of injustice to women in general. Besides this, there remains a bad perception that polygamy results in difficulties in maintaininga healthy marriage, and often leads to an unsuccessful marriage. In light of this, this study seeks to examine how the practice of polygamy affects the mental health status of family members involved, considering that most of the existing studies have found that polygamy is linked to mental health problems, especially among women and children. This conceptual paper presents the findings from previous studies and analyzes the association between polygamy and the mental health status of all family members affected by this practice. Previous studies revealed that families involved in polygamous marriages often do experience mental health problems, in particular women (most commonly the senior wife) and children. Many family members suffer symptoms of depression, anxiety, trauma, somatic symptom disorder, interpersonal sensitivity, phobias, obsessive-compulsive tendencies, paranoia and psychoticism. Counselors need to be aware of and pay attention to these issues, in order to enhance their competence in addressing mental health problems in polygamous households. Marriage and family counseling interventions need to be comprehensive in providing solutions and the optimal therapy should aim to help affected family members to function properly while ensuring their psychological well-being.